M2-based influenza vaccines: recent advances and clinical potential - Annasaheb Kolpe; Bert Schepens; Walter Fiers; Xavier Saelens (Taylor & Francis Group, 2017)
Introduction: Current influenza vaccines can prevent disease caused by influenza viruses but require annual administration and almost yearly reformulation. An attractive alternative approach would be to use a vaccine that provides broad and, ideally, lifelong protection against all influenza A and B virus strains. The extracellular domain of matrix protein 2 (M2e) of influenza A viruses is conserved and thus fits well in such a broadly protective vaccine. Areas covered: Recent advances in M2e vaccine design, the mode of action of M2e-based immunity and clinical progress of M2-based influenza vaccines. Expert commentary: Many M2e vaccine have been successfully tested for efficacy against a panel of divergent influenza viruses in animal models. More recently, clinical studies have been conducted with M2e vaccine candidates, which demonstrated their safety and immunogenicity in humans. Efficacy studies in humans are still needed to provide evidence that an M2e-based vaccine can protect against human influenza.